2017
DOI: 10.1111/ddi.12684
|View full text |Cite
|
Sign up to set email alerts
|

Combining point‐process and landscape vegetation models to predict large herbivore distributions in space and time—A case study of Rupicapra rupicapra

Abstract: Aim When modelling the distribution of animals under current and future conditions, both their response to environmental constraints and their resources’ response to these environmental constraints need to be taken into account. Here, we develop a framework to predict the distribution of large herbivores under global change, while accounting for changes in their main resources. We applied it to Rupicapra rupicapra, the chamois of the European Alps. Location The Bauges Regional Park (French Alps). Methods We bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Recent studies have highlighted the usefulness of including within the HSMs some predictors representing biotic interactions (Hof et al, 2012;Gherghel et al, 2018;Paiva-Silva et al, 2018) and/or the response of the resources used by animal species to the same abiotic variables used to model the species' potential distribution (Thuiller et al, 2018). Thus, for two selected pairs of closely related Neocrepidodera taxa, we implemented a nested modelling framework in which the predictions from Ensemble Models (EMs) built for the candidate host plants were included as predictors in the EMs built for the hosted flea beetles.…”
mentioning
confidence: 99%
“…Recent studies have highlighted the usefulness of including within the HSMs some predictors representing biotic interactions (Hof et al, 2012;Gherghel et al, 2018;Paiva-Silva et al, 2018) and/or the response of the resources used by animal species to the same abiotic variables used to model the species' potential distribution (Thuiller et al, 2018). Thus, for two selected pairs of closely related Neocrepidodera taxa, we implemented a nested modelling framework in which the predictions from Ensemble Models (EMs) built for the candidate host plants were included as predictors in the EMs built for the hosted flea beetles.…”
mentioning
confidence: 99%
“…Whilst powerful through its spatial extensiveness, spatial modelling of wildlife habitat and recreation indicators will need to be combined with other data sources including advanced analyses of social media images and trip reports, spatial tracking and social data. Further analyses also ought to incorporate climate change sensitivities, which are critical for multiple iconic high mountain vertebrates (Revermann et al, 2012;Thuiller et al, 2018;Zurell et al, 2012) and add to risks from human disturbance (Imperio et al, 2013). Likewise expected changes in outdoor recreation practices will need to be accounted for.…”
Section: Resultsmentioning
confidence: 99%
“…A study using DNA barcoding [30], on the other hand, showed that chamois can consume up to 110 different species. This difference has been attributed to the high level of resolution obtained with the DNA approach but also to the higher plant biodiversity of the study area (more than 1.500 species recorded, [73]). In fact, it is necessary to highlight the limitations related to dietary studies based on faecal cuticle microhistological analyses, such as ours.…”
Section: Discussionmentioning
confidence: 99%